THE EFFECT OF STUDYING THE YELLOW BOOK TOWARDS PAI LESSONS IN A CURRICULUM MANAGEMENT PERSPECTIVE - Arrohmatan Arrohmatan; Lisna Mualifah; Nasrudin Harahap; Nurul Hidayati Murtafiah (Al Wildan: Jurnal Manajemen Pendidikan Islam, 2022)
This study aimed to test and develop the theory of Condition of Learning by examining the presence or absence of the influence of yellow book learning on PAI subjects and then analyzing the effect of curriculum management perspectives, both supporting and inhibiting factors. This research uses a mixed quantitative and qualitative method, and data collection is carried out by observation, interviews, documentation and questionnaires. The results of research showed that PAI subjects were slightly influenced by yellow book learning with a percentage of 2.45%, meaning that other factors influenced 97.55%. Supporting factors the influence include, in planning the learning of the yellow book is positioned as the foundation of knowledge for PAI subjects, in its organization it is mastered by Kyai and Ustadz and is considered to have a high honorific value, in its implementation, The yellow books and PAI have many material similarities even more comprehensive, in its evaluation the learning of the yellow book is structured as PAI subjects. Meanwhile, the factor causing the low influence is that, in its planning, the yellow book learning reference is not balanced concerning PAI subjects, in its organization, the teacher is less competent so that students feel difficult, in its implementation, the yellow book learning is still less than optimal because it is not intensive in supporting PAI subjects. However, in its evaluation, the fundamental ideology is oriented toward cognitive knowledge so that few students get good grades.